Geochemical and microbiological profiles in hydrothermal extreme acidic environments (Pisciarelli Spring, Campi Flegrei, Italy). Issue 10 (26th July 2022) - Crognale, Simona; Venturi, Stefania; Tassi, Franco; Rossetti, Simona; Cabassi, Jacopo; Capecchiacci, Francesco; Bicocchi, Gabriele; Vaselli, Orlando; Morrison, Hilary G; Sogin, Mitchell L; Fazi, Stefano
Abstract: Although terrestrial hydrothermal systems are considered among the most fascinating environments, how their unique and extreme conditions can affect microorganisms selection and the role in biogeochemical cycles has not yet been well elucidated. A combined geochemical and microbiological exploration in waters and sediments from 10 sampling points along a sharp temperature gradient (15–90°C) within an extremely acidic hydrothermal system (Pisciarelli Spring, Campi Flegrei area, southern Italy) displayed how hydrothermal fluids influence the microbial dynamics. This area was characterized by high levels of reduced gaseous species (e.g. H2 S, H2, CH4, CO) and very low pH values (<2.3). Thermodynamic calculations revealed a high microbial catabolic potential in oxidation/reduction reactions of N-, S- and Fe-bearing species. Overall, an increase of the archaeal/bacterial abundance ratio was observed by decreasing temperature and pH values. In particular, Archaea and Bacteria were present in almost equal cell abundance (up to 1.1 × 10 9 and 9.3 × 10 8 cell/g, respectively) in the <70°C sampling points (average pH = 2.09); on the contrary, the highest temperature waters (85–90°C; average pH = 2.26) were characterized by a low abundance of archaeal cells. The high-throughput sequencing of the 16S rRNA genes indicated strong differences in archaeal and bacterial communities composition along the temperature gradient. However, the microbiome in this extreme environment was mainly constituted by chemoautotrophic microorganisms that were likely involved in N-, S- and Fe-bearing species transformations (e.g. Acidianus infernus, Ferroplasma acidarmanus, Acidithiobacillus, Sulfobacillus, Thaumarchaeota ), in agreement with thermodynamic calculations. Abstract : Differences in archaeal and bacterial communities composition along the temperature gradient were observed. The core microbiome in this extreme environment is mainly constituted by chemoautotrophic microorganisms, in agreement with thermodynamic calculations.